The Influence of Modernization on the Implementation of Passampo Siri' in Bugis Marriages in East Kolaka: Sociological Perspective of Islamic Law - Hartono, Rudi; Lestari, Ayu (Indonesian Journal of Islamic Law, 2022)
This research aims to analyze the influence of modernization on the implementation of Passampo Siri' in Bugis marriages in East Kolaka from a sociological perspective of Islamic law. Using a sociological approach to Islamic law and case study methods, this research involved in-depth interviews with traditional leaders, religious leaders, husband and wife couples, and people who understand Passampo Siri'. Data was also collected through participant observation and related documentation. The research results show that modernization has had a significant influence on the practice of Passampo Siri' in Bugis weddings, with changes in traditional elements such as mappacci and mappetettong ri ade' which have become more flexible due to adaptation to modern values. However, the core principles of Passampo Siri', namely maintaining family honor and the dignity of marriage, are still maintained. The sociological perspective of Islamic law supports the understanding that the changes in Passampo Siri' values are still in line with the principles of honor and dignity in Islamic teachings. Therefore, the strategy for preserving Passampo Siri' involves cultural education, outreach through religious and traditional leaders, strengthening traditional regulations, and strong traditional communities. This research recommendation emphasizes the importance of collaboration between local governments, traditional institutions, religious leaders, and the educational community to ensure harmonization between local culture and Islamic law in the modern era.